Are world cities also world immigrant cities? An international, cross-city analysis of global centrality and immigration. (June 2015) - Sanderson, Matthew R; Derudder, Ben; Timberlake, Michael; Witlox, Frank
Systematic research on world cities neglects immigration, despite its significance to world city formation. In this article, we test a foundational, but untested, premise of world cities research: that global centrality in the world urban system is associated with larger, more diverse immigrant populations. Using an international sample of cities, we conduct multivariate regressions of Benton-Short et al.'s Urban Immigrant Index on the Globalization and World City Network measure of advanced producer service firm centrality and two other measures of global urban centrality, controlling for competing explanations of international migration. Our findings reveal that cities that are more central to the network of advanced producer service firms have larger, more diverse immigrant populations than less-central cities. World cities are thus not only key sites for corporate control of the world economy, but they are also central in international flows of immigrant labor, as Sassen hypothesized nearly 30 years ago.